Research hotspots and trends of chordoma: A bibliometric analysis - Gao, Jianxuan; Huang, Runzhi; Yin, Huabin; Song, Dianwen; Meng, Tong (Frontiers in Oncology, 2022)
Background: Chordoma is a type of mesenchymal malignancy with a high recurrence rate and poor prognosis. Due to its rarity, the tumorigenic mechanism and optimal therapeutic strategy are not well known. Methods: All relevant articles of chordoma research from January 1st, 2000 to April 26th, 2022 were obtained from Web of Science Core Collection database. Blibliometrix was used to acquire basic publication data. Visualization and data table of collaboration network, dynamic analysis, trend topics, thematic map and factorial analysis were acquired using Blibliometrix package. VOSviewer was used to generate visualization map of co-citation analysis and co-occurrence. Results: A total of 2,285 articles related to chordoma were identified. The most influential and productive country/region was the United States, and Capital Medical University has published the most articles. Among all high-impact authors, Adrienne M Flanagan had the highest average citation rate. Neurosurgery was the important periodical for chordoma research with the highest total/average citation rate. We focused on four hotspots in recent chordoma research. The research of surgical treatment and radiotherapy was relatively mature. The molecule signaling pathway and targeted therapy, immunotherapy for chordoma were not yet mature, which will be the future trends of chordoma research. Conclusion: This study indicates that chordoma studies are increasing. Surgery and radiotherapy are well reported and always play fundamental roles in chordoma treatment. The molecule signaling pathway, targeted therapy and immunotherapy of chordoma are the latest research hotspots.